Survival Mechanisms Used by Some Leishmania Species to Escape Neutrophil Killing - Regli, Ivo B.; Passelli, Katiuska; Hurrell, Benjamin P.; Tacchini-Cottier, Fabienne (Frontiers in Immunology, 2017)
Neutrophils are the most abundant leukocytes in human blood. Upon microbial infection, they are massively and rapidly recruited from the circulation to sites of infection where they efficiently kill pathogens. To this end, neutrophils possess a variety of weapons that can be mobilised and become effective within hours following infection. However, several microbes including some Leishmania spp have evolved a variety of mechanisms to escape neutrophil killing using these cells as a basis to better invade the host. In addition, neutrophils are also present in unhealing cutaneous lesions where their role remains to be defined. Here, we will review recent progress in the field and discuss the different strategies applied by some Leishmania parasites to escape from being killed by neutrophils and as recently described for Leishmania mexicana, even replicate within these cells. Subversion of neutrophil killing functions by Leishmania is a strategy that allows parasite spreading in the host with a consequent deleterious impact, transforming the primary protective role of neutrophils into a deleterious one.